Unvaccinated COVID-19 Pneumonia- a family affair - Trilok Stead; Michael Hughes; Frank Fraunfelter; Vashun Rodriguez; Latha Ganti (Health Psychology Research)
The authors present the case of a 15-year-old boy who was infected with COVID-19 by his family and developed pneumonia severe enough to require hospitalization. He was one of several children who required hospitalization, and vaccination was considered by the parent to be "risky" despite this. This case illustrates the complexities of vaccine hesitancy and societal misinformation.